Non‐linear 3D modelling of RC slab punching shear failure - Vainiunas, Povilas; Popovas, Vladimiras; Jarmolajev, Andrej (Journal of Civil Engineering and Management, 2004)
Modern technologies of 3D computer modelling with the help of finite‐element methods of numerical analysis in non‐linear aproach enable a reliable simulation of real reinforced concrete slabs behaviour under the conditions of complicated stress‐strain state in all the stages of their behaviour under loading, including a stage of elasticity‐plasticity state in concrete and reinforcement as well as formation and development of destruction mechanism. Numerical methods of modelling of critical behaviour of structures go beyond the borders of scientific research, being increasingly applied for solving non‐trivial engineering tasks when it becomes evident that possibilities of analytical approach, acceptable for the existing design codes are not sufficient. In such a case an exceptional attention is to be paid for verification of calculated models against experimental research of similar numeric models. This article reviews a case of complex experimental‐theoretical and numerical calculation and analysis methods applied for a reinforced concrete floor slab and column connection. The object of research is of exceptional interest as for practical calculation methods for this type of constructions following design norms of different countries revision and additional processing are necessary. The results of the reinforced concrete floor slab and column junction computer model non‐linear numerical analysis are presented and compared with the results of an experimental study. First Published Online: 14 Oct 2010